Critical success factors during the implementation of ISO 22000:2018 - Monge-Mora, P. M. (2020)
Purpose: The purpose of the paper is to evaluate why companies still struggle with ISO 22000 implementation and maintenance, identifying which aspects are key for its success. Design/methodology/approach - A literature review was carried out based on Scientific articles and implementation guides collected from Google Scholar, ScienceDirect and ResearchGate. Findings - Nine aspects seem to have a broader impact on organizations maintenance of ISO 22000 and other FSMS. Furthermore, the empirical research reveals that having an efficient food safety management system is a prerequisite for companys competitiveness. Practical implications - The findings show that many of the critical success factors for a FSMS implementation are based on regular and adequate management of people inside the company. Originality/value - A novel model of segmenting critical success factors is presented, which has practical implications for ISO 22000 achievement.